Kachru’s Indigenization: A Potent Voice and Pathway towards Decolonization in P’Bitek’s Song of Lawino: https://doi.org/10.55966/assaj.2025.4.1.0104 - Zahid Salim; Dr. Muhammad Shakil Ur Rehman; Shams Ur Rehman (`, 2025)
P’Bitek’s acclaimed African work, Song of Lawino (1966) explores the complexities and conflicts of indigenous cultural identity and recognition grappled with the imposed colonization. Through the potent voice of an Acholi woman, Lawino challenges the western imperial effects on African culture, identity and values. She is extremely disappointed after her husband, Ocol’s rejection of native culture and values in favor of the Western. This paper offers the reading of the African selected work through Braj Kachru’s model of Indigenization to delve deep into the implicit agenda of colonization against the natives. Moreover, this study can provide an understanding to unfold the impact of colonization on Africans that has been fictionally represented in Song of Lawino (1966). Therefore, the present study examines to highlight how important and significant it is to project your own culture and identity that will go a long way towards decolonizing the indigenous lands under the occupation of colonial powers. The poet in his seminal and representative work in African oral literature suggests a way out to see the light at the end of the dark tunnel through projection of indigenization. Hence, indigenization is a potent voice towards decolonization and the research provides an alternative understanding to what colonists and imperialists manufacture and shape their discourse regarding colonized. Keywords: Kachru, African Oral Literature, Indigenization, Potent Voice, Decolonization, P’Bitek, Song of Lawino